Emerging of leishmaniasis in Zamzum, Libya (Sirte Journal of Medical Sciences, 2022)
A pilot study on leishmaniasis was carried in the outpatient clinic, Zamzam, Libya, from 4 October 2018 to 31 May 2019. A total of 84 patients with cutaneous leishmaniasis (CL) were studied. The duration of the lesions varied from a few days to 3 months. Multiple lesions ranging from one to 21 were present in 78% of cases. Ulcerative lesions were found in 37%, nodulo-ulcerative in 22%, nodular in 30% and others, including infiltrated, fungating and warty lesions, in 3% of patients. The lower limbs were involved in 66%, upper limbs in 36% (Figure. 1), face in 89%, back in 6%, chest in 1%, and abdomen in 2%. Lesions were also found on the ear, scalp, genitalia and mucocutaneous junctions. Lymphatic involvement was present in 9% of the patients, secondary infection in 10%, fever in 12%, and pain in 40% and itching in 72%. Features of diffuse cutaneous leishmaniasis were noted in 3 patients. Slit skin smear was positive for parasites in 67 cases (highly positive in 34 cases). Various therapeutic regimens are discussed. Only patients with severe lesions (approximately 21%) were given 3 to 4 weeks' treatment with intravenous Pentostam, to which all except 4 responded satisfactorily with minimal side effects
Keywords: leishmaniasis; Emergenig disease; Cutaneous leishmaniasis